2003
DOI: 10.1001/archpsyc.60.3.296
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation of the Subthalamic Nucleus Enhances Emotional Processing in Parkinson Disease

Abstract: Deep brain stimulation of the subthalamic nucleus selectively enhanced affective processing and subjective well-being and seemed to be antidepressive. Levodopa and deep brain stimulation had similar effects on emotion. This finding may provide new clues about the neurobiologic bases of emotion and mood disorders, and it illustrates the important role of the basal ganglia and the dopaminergic system in emotional processing in addition to the well-known motor and cognitive functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 139 publications
(91 citation statements)
references
References 52 publications
(53 reference statements)
3
81
0
6
Order By: Relevance
“…STN-DBS itself has a positive eff ect on offperiod apathy, contributing to improvement of off -period cognitive and emotional aspects in apathy. 92,[104][105][106] However, with regard to the on-period motivational aspects of the antiparkinsonian drugs, a slowly progressive desensitisation of the psychotropic eff ects of dopaminergic treatment after drug decrease 107 explains why the hypodopaminergic withdrawal syndrome in patients on chronic STN-DBS typically occurs with a substantial delay of several months after surgery 83,92 (unlike the much more acute withdrawal syndrome after cessation of dopamine agonists in patients not receiving chronic STN-DBS). 93 The potential to reverse postoperative apathy after D2 or D3 receptor stimulation with oral dopamine receptor agonists 108,109 clearly suggests a Parkinson's disease-related symptom that has been unmasked by a decrease in drug treatment.…”
Section: Apathy After Deep Brain Stimulation In Parkinson's Diseasementioning
confidence: 99%
“…STN-DBS itself has a positive eff ect on offperiod apathy, contributing to improvement of off -period cognitive and emotional aspects in apathy. 92,[104][105][106] However, with regard to the on-period motivational aspects of the antiparkinsonian drugs, a slowly progressive desensitisation of the psychotropic eff ects of dopaminergic treatment after drug decrease 107 explains why the hypodopaminergic withdrawal syndrome in patients on chronic STN-DBS typically occurs with a substantial delay of several months after surgery 83,92 (unlike the much more acute withdrawal syndrome after cessation of dopamine agonists in patients not receiving chronic STN-DBS). 93 The potential to reverse postoperative apathy after D2 or D3 receptor stimulation with oral dopamine receptor agonists 108,109 clearly suggests a Parkinson's disease-related symptom that has been unmasked by a decrease in drug treatment.…”
Section: Apathy After Deep Brain Stimulation In Parkinson's Diseasementioning
confidence: 99%
“…However, the vast majority of cases with an acute emotional response to STN DBS exhibit hypomania [50] or mania [25,52]. More importantly, a systematic study of a large number of PD patients revealed a mood effect of acute STN DBS that corresponds to subjective wellbeing or euphoria, and not depression [23,59]. Single case reports have also shown that dysphoria during the off-medication period is improved by STN DBS [60][61][62].…”
Section: The Stn and Impulsivitymentioning
confidence: 99%
“…23,24 Previous studies have used acute effects of STN DBS as a tool to modify the activity in basal ganglia circuits intraindividually. [25][26][27][28][29][30] To evaluate the possible influence of STN stimulation on spatial orientation, we assessed 12 patients with Parkinson's disease (PD) after implantation of electrodes in the STN for chronic DBS in four conditions: turning both stimulators OFF, turning ON only the right stimulator, turning ON only the left stimulator, and turning ON both stimulators. After overnight withdrawal of L-dopa, patients were pseudorandomly assigned to one of the stimulation conditions.…”
mentioning
confidence: 99%